2007
DOI: 10.1016/j.healun.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Fibrinolytic Cascade Post-transplant: Evidence of a Bimodal Expression Pattern

Abstract: Changes in the fibrinolytic system that occur after cardiac transplantation (CTx) and the factors which influence such changes are poorly described, yet may be ultimately important in determining the varying morphologic features of transplant related coronary artery disease (Tx CAD). Baselines demographic, as well as serial clinical information and plasma fibrinolytic levels were prospectively recorded preCTx and multiple times postCTx in 110 de novo cardiac transplant recipients. We noted a biphasic change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Impaired fibrinolysis also plays a role in CAV pathogenesis. Decreased plasmin production and increased fibrin deposition are common features of grafts with angiographically detectable CAV (27). Vascular tPA depletion (12), plasminogen activator inhibitor‐1 overexpression (28) and perturbations in their balance (27) promote CAV following transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired fibrinolysis also plays a role in CAV pathogenesis. Decreased plasmin production and increased fibrin deposition are common features of grafts with angiographically detectable CAV (27). Vascular tPA depletion (12), plasminogen activator inhibitor‐1 overexpression (28) and perturbations in their balance (27) promote CAV following transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased plasmin production and increased fibrin deposition are common features of grafts with angiographically detectable CAV (27). Vascular tPA depletion (12), plasminogen activator inhibitor‐1 overexpression (28) and perturbations in their balance (27) promote CAV following transplantation. Fibrin deposits following ischemia‐reperfusion, which would normally be removed by fibrinolytic activation, persist if there is early loss of tPA, which may partially explain why tPA depletion was the dominant predictor in our models.…”
Section: Discussionmentioning
confidence: 99%
“…4 Indeed, an enhanced fibrinolytic phase, characterized by low PAI-1 and retained PA/plasmin activity, occurs within the first year after CTx and corresponds to the height of pathologic intimal development seen clinically. In this regard, vascular injury secondary to the transplant procedure results in the activation of this system and increased plasmin/PA activity, a process similar to that which occurs after angioplasty.…”
Section: Discussionmentioning
confidence: 98%
“…We have demonstrated previously that by the end of the first year after CTx, an impaired fibrinolytic state with heightened PAI-1 activity and reduced plasmin activity exists within a recipient's blood. 4 Furthermore, angiographically visible TxCAD is more likely to develop in recipients who receive hearts from donors with certain PAI-1 polymorphisms that code for enhanced PAI-1 activity. 8 Thus, conditions or genetic variants that support a prothrombotic state later after transplantation correlate well with the microvascular fibrin deposition characteristic of mature TxCAD described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that following the initial perioperative reduction in PAI-1 causing hyperfibrinolysis in cardiac transplant patients PAI-1 levels are then significantly increased over the following 12 months post-transplant, possibly explaining features of transplantrelated coronary artery disease. 6 The liver is the main site of synthesis and metabolism of the majority of stimulatory and inhibitory coagulation and fibrinolytic factors. For this reason liver disease and liver surgery are often associated with complex coagulopathies.…”
Section: Incidence Of Hyperfibrinolysismentioning
confidence: 99%